Предание о ритуальном поясе - Арутюнян, Саргис (Зангак-97)
The article is a section from the author’s voluminous book on Armenian mythology which was published in Armenian in Beirut in 2000 and immediately became a rarity. The idea of the belt is presented through etiological legends about a concrete landscape in the Armenian Highland and through myths dealing with more general anthropomorphic models of the world. To understand the significance of the belt in various mythological systems, the author analyzes ethnographic traditions related with belts, as well as archaeological evidences of belt usage on the territory of present-day Armenia. The idea of belt and belting is also discussed in the context of the semantic field of the Armenian words designating belt.
Keywords: Этнография; Фольклор